Modeling the formation of 2, 3, 7, 8-tetrachlorodibenzo-p-dioxin in the historical manufacture of 2, 4, 5-trichlorophenol. Issue 4 (2nd October 2017) - Parette, Robert; McCrindle, Robert; McMahon, Katherine S.; Watson, Valerie J.; Janik, Michael J.; Velegol, Darrell; Dorman, Frank L.; Pearson, Wendy N.
ABSTRACT: A universal model for the simulation of 2, 3, 7, 8-tetrachlorodibenzo- p -dioxin concentrations in the historical manufacture of 2, 4, 5-trichlorophenol was developed. The model successfully simulates the conversion of 1, 2, 4, 5-tetrachlorobenzene to 2, 4, 5-trichlorophenol, and modeled the concentrations of 2, 3, 7, 8-tetrachlorodibenzo- p -dioxin with an r 2 of .941 against measured data from 38 experimental runs. The high r 2 supports the proposed formation mechanism (second order with respect to 2, 4, 5-trichlorophenol). Simultaneous degradation of 2, 3, 7, 8-tetrachlorodibenzo- p -dioxin by methoxylation/hydroxylation was hypothesized to play a role; however, modeling indicated this was insignificant in the industrial production of 2, 4, 5-trichlorophenol. This model can be a useful tool in environmental forensic investigations of sites where 2, 4, 5-trichlorophenol was produced.